The rise in the contribution of denitrification is the primary reason for the increase of N2O emissions in the Anthropocene - Huining Tang; Ruiyang Xia (PLoS ONE, 2025)
Nitrous oxide (N2O) is the fastest growing category of greenhouse gases in the recent decades. This study systematically summarized the causes of increased N2O emissions and proposed targeted mitigation strategies based on isotopic analysis. The increase in annual N2O emissions is mainly derived from microbial processes in agricultural soils and eutrophic waters, where denitrifiers are responsible for the anthropogenic emissions. In natural soil and water, minor N2O emissions are accompanied by a significant contribution of nitrification. Since the industrialization and urbanization, the extensive utilization and leaching of fertilizers, and the sewage discharge, have significantly facilitated the denitrification activity. For example, the contribution of denitrification to N2O emissions in the grassland and forest soils increased from approximately 50% to 80% after fertilization, similar phenomena have also been observed in eutrophic waters. Human disturbances enhanced N2O emissions by increasing the contribution of denitrification to N2O production. Therefore, the targeted mitigation strategies lie in the effective control of fertilizer and organic pollutant, the improvement of aeration, as well as the microbial control in fertilized soils and eutrophic waters. This study is of great significance in improving our understanding of N2O emission increase and provides a foundation for the development of effective mitigation strategies.